2018
DOI: 10.21037/jtd.2018.01.125
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high-flow nasal cannula oxygen therapy for acute respiratory failure with hypercapnia

Abstract: Background: Heated and humidified high-flow nasal cannula (HFNC) oxygen therapy has recently been introduced for hypoxic respiratory failure. However, it has not been well-evaluated for acute respiratory failure with hypercapnia. Methods: This retrospective study included acute respiratory failure patients with hypercapnia in the medical intensive care unit (MICU) from April 2011 to February 2013, who required HFNC oxygen therapy for hypoxemia. Respiratory parameters were recorded and arterial blood gas analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 19 publications
3
52
1
5
Order By: Relevance
“…Results of this study suggest that HFOT could be an alternative option when NIV tolerance compromises continuation of treatment. A retrospective study including 33 COPD patients with hypoxaemia and hypercapnia showed that the application of HFOT after failure of standard oxygen, NIV or intolerance to NIV resulted in improvement of pCO 2 after 1 and 24 h of treatment initiation . In another observational study, Lee et al .…”
Section: Niv As First‐line Treatment For Acute Respiratory Acidosis Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of this study suggest that HFOT could be an alternative option when NIV tolerance compromises continuation of treatment. A retrospective study including 33 COPD patients with hypoxaemia and hypercapnia showed that the application of HFOT after failure of standard oxygen, NIV or intolerance to NIV resulted in improvement of pCO 2 after 1 and 24 h of treatment initiation . In another observational study, Lee et al .…”
Section: Niv As First‐line Treatment For Acute Respiratory Acidosis Dmentioning
confidence: 99%
“…Indeed, previous studies showing potential benefits of HFOT in ARF did not include patients with hypercapnia. Up until now, only a few smaller studies and case reports with hypercapnic patients have been published. However, studies conducted in emergency departments comparing HFOT with standard oxygen or NIV included larger samples of patients with ARF of various causes and, especially, COPD exacerbation .…”
Section: Niv As First‐line Treatment For Acute Respiratory Acidosis Dmentioning
confidence: 99%
“…3,16 The utility of HHFNC in hypercapnic respiratory failure is still uncertain. 7,17 It is seen as a useful alternative in a patient who does not tolerate NIV. 3 What are the contraindications for HHFNC?…”
Section: What Are the Indications For Hhfnc?mentioning
confidence: 99%
“…Recently, some studies showed the beneficial effects of heated humidification therapy on mucociliary clearance and ventilation in patients with bronchiectasis [16,17] and COPD [18,19,20], both muco-obstructive diseases characterized by airway inflammation, mucus hypersecretion and impaired mucociliary transport [21]. Nevertheless, few data exist about the use of HFNT for the treatment of bronchiectasis and bronchiectasis-COPD exacerbations.…”
Section: Introductionmentioning
confidence: 99%